Ulipristal acetate simultaneously provokes antiproliferative and proinflammatory responses in endometrial cancer cells. Issue 1 (January 2022) - Kanda, Ranka; Miyagawa, Yuko; Wada-Hiraike, Osamu; Hiraike, Haruko; Nagasaka, Kazunori; Ryo, Eiji; Fujii, Tomoyuki; Osuga, Yutaka; Ayabe, Takuya
Abstract: Ulipristal acetate (UPA), a selective progesterone receptor modulator, is used for the treatment of uterine fibroids and selectively inhibits the proliferation and inflammation of leiomyoma cells. As few studies have focused on the molecular biological mechanism of UPA in Ishikawa endometrial cancer cells, we aimed to identify the effects of UPA on these cells. Ishikawa cells were treated with different concentrations of UPA. Cell viability and colony formation assays were performed to assess the growth of cancer cells, whereas invasion and migration assays were used to measure cell motility and invasiveness. Western blotting, caspase 3/7 assay, TUNEL assay, and flow cytometry were performed to analyze apoptosis. Moreover, expression levels of the proinflammatory cytokines oncostatin M, its receptor, interleukin 6, and interleukin 8 were examined using quantitative real-time PCR. UPA decreased cell viability and growth, thereby inhibiting cell migration and invasion via induction of apoptosis. Contrary to expectation, stand-alone application of UPA increased the expression of the proinflammatory cytokines but concomitant use of UPA and the estrogen receptor antagonist ICI 182, 720 decreased it. These data revealed a novel dual role of UPA: It could attenuate cell growth via activation of apoptosis while simultaneously provoking the activation of proinflammatory cytokines in endometrial cancer cells. These indicate that the combination of UPA and an estrogen receptor antagonist may be useful in suppressing the secretion of proinflammatory cytokines by UPA alone. Highlights: A selective progesterone receptor modulator ulipristal acetate, used for the treatment of uterine fibroids and selectively inhibits the proliferation and inflammation of leiomyoma cells decreased cell viability and growth in Ishikawa endometrial cancer cells. Ulipristal acetate induced apoptosis in endometrial cancer cells and activated oncostatin M, IL-6, IL-8 known as proinflammatory cytokine. Combination of Ulipristal acetate and estrogen receptor antagonist downregulated proinflammatory cytokine in endometrial cancer cells. Abstract : Ulipristal acetate; Selective progesterone receptor modulator; Progesterone receptor modulator–associated endometrial change; Apoptosis; Proinflammatory cytokine.